Inhibiting PGGT1B Disrupts Function of RHOA, Resulting in T-cell Expression of Integrin α4β7 and Development of Colitis in Mice - Lopez Posadas, Rocío; Fastancz, Petra; Martínez-Sánchez, Luz del Carmen; Panteleev-Ivlev, Julia; Thonn, Veronika; Kisseleva, Tatyana; Becker, Lukas S.; Schulz-Kuhnt, Anja; Zundler, Sebastian; Wirtz, Stefan; Atreya, Raja; Carlé, Birgitta-Elisabeth; et al. (Gastroenterology, 2019)
Background & Aims: It is not clear how regulation of T-cell function is altered during development of inflammatory bowel diseases (IBD). We studied the mechanisms by which geranylgeranyltransferase-mediated prenylation controls T-cell localization to the intestine and chronic inflammation. Methods: We generated mice with T-cell–specific disruption of the geranylgeranyltransferase type I, beta subunit gene (Pggt1b), called Pggt1bΔCD4 mice, or the ras homolog family member A gene (Rhoa), called RhoaΔCD4 mice. We also studied mice with knockout of CDC42 or RAC1 and wild-type mice (controls). Intestinal tissues were analyzed by histology, multiphoton and confocal microscopy, and real-time polymerase chain reaction. Activation of CDC42, RAC1, and RHOA were measured with G-LISA, cell fractionation, and immunoblots. T cells and lamina propria mononuclear cells from mice were analyzed by flow cytometry or transferred to Rag1–/– mice. Mice were given injections of antibodies against integrin alpha4beta7 or gavaged with the RORC antagonist GSK805. We obtained peripheral blood and intestinal tissue samples from patients with and without IBD and analyzed them by flow cytometry. Results: Pggt1bΔCD4 mice developed spontaneous colitis, characterized by thickening of the intestinal wall, edema, fibrosis, accumulation of T cells in the colon, and increased expression of inflammatory cytokines. Compared with control CD4+ T cells, PGGT1B-deficient CD4+ T cells expressed significantly higher levels of integrin alpha4beta7, which regulates their localization to the intestine. Inflammation induced by transfer of PGGT1B-deficient CD4+ T cells to Rag1–/– mice was blocked by injection of an antibody against integrin alpha4beta7. Lamina propria of Pggt1bΔCD4 mice had increased numbers of CD4+ T cells that expressed RORC and higher levels of cytokines produced by T-helper 17 cells (granulocyte-macrophage colony-stimulating factor, interleukin [IL]17A, IL17F, IL22, and tumor necrosis factor [TNF]). The RORC inverse agonist GSK805, but not antibodies against IL17A or IL17F, prevented colitis in Pggt1bΔCD4 mice. PGGT1B-deficient CD4+ T cells had decreased activation of RHOA. RhoAΔCD4 mice had a similar phenotype to Pggt1bΔCD4 mice, including development of colitis, increased numbers of CD4+ T cells in colon, increased expression of integrin alpha4beta7 by CD4+ T cells, and increased levels of IL17A and other inflammatory cytokines in lamina propria. T cells isolated from intestinal tissues from patients with IBD had significantly lower levels of PGGT1B than tissues from individuals without IBD. Conclusion: Loss of PGGT1B from T cells in mice impairs RHOA function, increasing CD4+ T-cell expression of integrin alpha4beta7 and localization to colon, resulting in increased expression of inflammatory cytokines and colitis. T cells isolated from gut tissues from patients with IBD have lower levels of PGGT1B than tissues from patients without IBD.
CRIS-Team Scopus Importer:2019-10-08
Keywords: IBD; Immune Regulation; Mouse Models; Prenylation